2017
DOI: 10.1371/journal.pone.0184807
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical characterization of the Vochysia rufa (Vochysiaceae) extract and its effects on oxidative stress in the pancreata of streptozotocin-induced diabetic rats

Abstract: Aqueous extract of macerated Vochysia rufa stem bark has been commonly used in the treatment of diabetes. Therefore, we evaluated the antihyperglycemic and antioxidant effects of an extract of V. rufa on the pancreata of streptozotocin (STZ)-induced diabetic rats. Animals received one of the following treatments daily by oral gavage: water (diabetic-control), V. rufa extract (diabetic-V. rufa), or glibenclamide (diabetic-GBD). Total antioxidant capacity; levels of thiobarbituric acid reactive substances, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
(54 reference statements)
2
1
0
Order By: Relevance
“…Our results showed that serum renal parameters, urea and creatinine concentrations, changed in the tested groups. Other researchers demonstrated increase in the level of serum urea and creatinine in the diabetic animals (Latifi et al 2019;Saeed et al 2008;de Gouveia et al 2017;Xue et al 2017;Chayarop et al 2017). In our research DM did not increase the serum creatinine level, but its level was increased in the group of diabetic rats treated with folic acid.…”
Section: Discussionsupporting
confidence: 48%
“…Our results showed that serum renal parameters, urea and creatinine concentrations, changed in the tested groups. Other researchers demonstrated increase in the level of serum urea and creatinine in the diabetic animals (Latifi et al 2019;Saeed et al 2008;de Gouveia et al 2017;Xue et al 2017;Chayarop et al 2017). In our research DM did not increase the serum creatinine level, but its level was increased in the group of diabetic rats treated with folic acid.…”
Section: Discussionsupporting
confidence: 48%
“…The gender Vochysia has abundant polyphenols and triterpenes 38 with antidiabetic properties, 39 but the total polyphenols, flavonoids and condensed tannins content were only recently revealed for Vochysia rufa ethanolic extract of stem bark. Moraes et al 17 and Gouveia et al 18 using the same aqueous extract of the present study concluded that hepatic and pancreatic oxidative stress, respectively, caused by streptozotocin-induced diabetes, reduced after treatment. Moreover, Gouveia et al 40 revealed partial composition of Vochysia rufa stem bark and its effect against oxidative damage in endothelial cells, and in the Vochysia rufa extract was found to be composed of free sugars (inositol, galactose, glucose, mannose, sucrose, arabinose, and ribose) as the main metabolites.…”
Section: Resultssupporting
confidence: 69%
“…Inositol, galactose, glucose and mannose with m / z of 179; sacarose with m / z of 341; arabinose and ribose with m / z of 149 have been previously identified in the extract. LC-MS analyses also suggested the presence of phenolic compounds of flavonoid type [ 15 , 20 ].…”
Section: Resultsmentioning
confidence: 99%